(untitled) (Universal International Scientific Journal, 2026)
This article analyzes the poetic and stylistic functions of the metaphor of time in literary texts. The metaphor of time is an important artistic tool for expressing the author’s idea in a literary work, revealing the mental state of images, and enhancing the aesthetic impact of the work. The study studies the semantic layers, stylistic functions, and role of the metaphor of time in creating a poetic image based on scientific and methodological approaches. Also, the interpretation of the metaphor of time in the literary traditions of the East and the West is analyzed comparatively, and their specific stylistic features are identified. The results of the study are of significant scientific importance in the stylistic and poetic analysis of the literary text.